Rescue policies for small businesses in the COVID-19 recession - Alessandro Di Nola; Leo Kaas; Haomin Wang (Leibniz Institute for Financial Research SAFE, 2022)
While the COVID-19 pandemic had a large and asymmetric impact on firms, many countries quickly enacted massive business rescue programs which are specifically targeted to smaller firms. Little is known about the effects of such policies on business entry and exit, factor reallocation, and macroeconomic outcomes. This paper builds a general equilibrium model with heterogeneous and financially constrained firms in order to evaluate the short- and long-term consequences of small firm rescue programs in a pandemic recession. We calibrate the stationary equilibrium and the pandemic shock to the U.S. economy, taking into account the factual Paycheck Protection Program (PPP) as a specific grant policy. We find that the policy has only a small impact on aggregate employment because (i) jobs are saved predominately in less productive firms that account for a small share of employment and (ii) the grant induces a reallocation of resources away from larger and less impacted firms. Much of this reallocation happens in the aftermath of the pandemic episode. While a universal grant reduces the firm exit rate substantially, a targeted policy is not only more cost-effective, it also largely prevents the creation of "zombie firms" whose survival is socially inefficient.
Keywords: E22; E65; G38; H25; 330; COVID-19; Heterogeneous Firms; Business Subsidies; Paycheck Protection Program